Macrophage-derived CXCL9 and CXCL11 recruit CD8 T cells in skin and provide long-term disease control in mogamulizumab-treated CTCL patients. (October 2021) - de Masson, Adèle; Darbord, Delphine; Dobos, Gabor; Boisson, Marie; Roelens, Marie; Ram-Wolff, Caroline; Cassius, Charles; Le Buanec, Hélène; de la Grange, Pierre; Jouenne, Fanélie; Louveau, Baptiste; Sadoux, Aurélie; et al.
Abstract : Cutaneous T-cell lymphoma (CTCL) is a malignancy of skin-homing T-cells. Long-term remissions are rare in CTCL, and the pathophysiology of long-lasting disease control is unknown. Mogamulizumab is a defucosylated anti-human CCR4 antibody that depletes CCR4-expressing CTCL tumor cells and peripheral blood memory regulatory T cells. Prolonged remissions and immune side effects have been observed in mogamulizumab-treated CTCL patients. We report that mogamulizumab induced skin rashes in 32% of 44 CTCL patients. These rashes were associated with long-term CTCL remission, even in the absence of specific CTCL treatment. CTCL patients with mogamulizumab-induced rash had significantly higher overall survival (hazard ratio, 0.15 (0.05–0.45, p=0.03). Histopathology and immunohistochemistry of the rashes revealed granulomatous and lichenoid patterns with CD163 macrophagic and CD8 T-cell infiltrates. Depletion of skin CTCL cells was confirmed by high-throughput sequencing analysis of TCRβ genes and in blood by flow cytometry. New reactive T-cell clones were recruited in skin. Gene expression analysis showed overexpression of CXCL9 and CXCL11, two chemokines involved in CXCR3-expressing T-cell homing to skin. Single-cell RNA sequencing analysis in skin of CTCL patients confirmed that CXCL9 and CXCL11 were primarily macrophage derived and that skin T-cells expressed CXCR3. Finally, patients with rashes had a significantly higher proportion of exhausted reactive blood T-cells expressing TIGIT and PD1 at baseline compared to patients without rash, which decreased under mogamulizumab treatment, consistent with an activation of the antitumor immunity. Together, these data suggest that mogamulizumab may induce long-term immune control in CTCL patients by activation of the macrophagic and T-cell immune responses.